Keo, Chetra (audio interview #4 of 5) - Keo, Chetra; Pierce, Mark, interviewer
<>INTERVIEW DESCRIPTION<> - This is the fourth of five interviews conducted over a three month period with Chetra Keo, a friend of the interviewer. As before, the interview was conducted in Keo's room, late at night. It should be noted that the segments in this interview tend to be rather long. 12/9/1989